LANDASAN MANAJEMEN PENDIDIKAN ISLAM - Ahsantudhonni; Muhammad Arif Syihabuddin (Cendekia, 2019)
The purpose of this research is to explain and analyze the foundation of Islamic Education Management. This research is important to do, because the development of Islamic Religious Education cannot be separated from the contribution of management in an organization of Islamic Education Institutions. Management in an Islamic Education Institution organization certainly has a foundation, so that the management of Islamic Education institutions will run well. The method used in this research is library research. Which means the researcher collected various literatures in the form of books, journals and research results that have been done before and are relevant to this research. The results of this study explain that there are four foundations in Islamic Education Management. These include theological foundation, rational foundation, empirical foundation and theoretical foundation.